ANALISIS KEMAMPUAN PEMAHAMAN KONSEPTUAL SISWA PADA MATERI PECAHAN KELAS V SD NEGERI 06 SELAKAU - Hendriana, Evinna Cinda; Nurhadi, Dendi; Nurhayati, Nurhayati (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2023)
This study aims to describe students' conceptual understanding abilities in class V fraction material at SDN 06 Selakau. The research used is descriptive qualitative research. The subjects of this study were fifth grade students at SD Negeri 06 Selakau. The object of this research is the ability of students' conceptual understanding in mathematics in class V SDN 06 Selakau. The results showed that students' conceptual understanding abilities for each category were 16.6% of students who had high conceptual understanding abilities and 33.3% of students who had low conceptual understanding abilities while 50% of these students had moderate conceptual understanding abilities. From the results of the highest percentage per indicator is 55.2% achievement in the indicator of presenting the concept in various forms of mathematical representation, while the lowest is in the indicator of using, utilizing, and selecting certain procedures or operations with 51.04% achievement. Thus, most of the factors that influence students' conceptual understanding abilities are that students are unable to understand the questions and concepts referred to by the questions given, and still rely on answers from friends and parental assistance.